2015
DOI: 10.3892/ol.2015.3950
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of cyclooxygenase-2 and interleukin-32 in primary gastric B-cell lymphoma

Abstract: Abstract. Cyclooxygenase-2 (COX-2) and interleukin-32 (IL-32) expression has been examined in various carcinomas and inflammations, and has been suggested to be significant in tumor progression and prognosis. The present study was conducted to investigate the expression of COX-2 and IL-32 in primary gastric B-cell lymphoma in order to define their clinical significance and their association with Helicobacter pylori (Hp) infection. COX-2 and IL-32 protein expression was detected in 31 primary gastric B-cell lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In this study the role of cytokine IL-32 was demonstrated in psoriatic patients. IL-32 was first discovered in IL-2-activated T cells and natural killer cells [ 11 , 12 , 13 ] and now it is well established that IL-32 exhibits numerous classical proinflammatory activities [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It stimulates the production of TNF-α, IL-1β, IL-6, INF-γ, IL-8, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the role of cytokine IL-32 was demonstrated in psoriatic patients. IL-32 was first discovered in IL-2-activated T cells and natural killer cells [ 11 , 12 , 13 ] and now it is well established that IL-32 exhibits numerous classical proinflammatory activities [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It stimulates the production of TNF-α, IL-1β, IL-6, INF-γ, IL-8, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance, IL-32 exhibits numerous classical proinflammatory activities [ 13 , 14 , 15 , 16 , 17 , 18 ]. It stimulates the production of numerous proinflammatory cytokines including TNF-α, IL-1β, and IL-6 [ 13 , 19 , 20 , 21 , 22 ]. It also activates key proinflammatory cell signaling pathways such as mitogen-activated protein kinase (MAPK)-p38, extracellular receptor kinases (ERK), and nuclear transcription factor (NF)-κB in various cell types [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al . also showed (58) that IL-32 and COX2 expressions were significantly correlated with greater H. pylori infection, more frequent lymph node metastasis, and advanced stages of gastric B-cell lymphoma. In addition, patients with higher COX2 and IL-32 levels showed a poorer prognosis compared with those patients with lower COX2 and IL-32 levels, but the difference was not statistically significant.…”
Section: Role Of Il-32 In Other Types Of Cancermentioning
confidence: 94%
“…IL-32 and COX2 expressions were immunohistochemically detected in 31 primary gastric B-cell lymphoma patients and 19 chronic gastritis patients, and were significantly higher in H. pylori + lymphoma tissues compared with H. pylori − lymphoma tissues (58). This is reasonable because an increase in COX2 in the human stomach is associated with H. pylori infection (59, 60) and COX2 increases IL-32 expression (61).…”
Section: Role Of Il-32 In Other Types Of Cancermentioning
confidence: 99%
“…Cui et al [ 5 ] investigated human gastric ENMZL with respect to cyclooxygenase-2 (COX-2) and interleukin-32 (IL-32) expression since these have been suggested to be significant in tumor progression and prognosis. COX-2 and IL-32 protein expression was higher in 31 primary gastric B cell lymphoma patients compared to 19 chronic gastritis patients, especially so in patients who had HP-positive lymphomas; the expression level of COX-2 was positively correlated with the expression level of IL-32.…”
Section: Biology Of Lymphomamentioning
confidence: 99%